Справочник по буровзрывным работам - Друкованый М. Ф. Михаил Федорович; Дубнов Л. В. Лев Владимирович; Миндели Э. О. Элизбар Онисимович; Иванов К. И. Константин Иванович; Ильин В. И. Виктор Иванович (Москва, Недра, 1976)
Авторы указаны на обороте титульного листа.